UiTMLaw retains its 6 stars performance - UiTM, Faculty of Law (Faculty of Law, 2023)
This award is granted in recognition of the faculty's success in meeting UiTM's Key Performance Indicators (KPIs) in numerous areas. It is the result of the synergized cooperation of all members of the UiTMLaw family in working towards realizing our objectives. As one of the top legal education institutions in Malaysia, UiTMLaw strives to be the best and in doing so, remain consistent in operating to the best of its capabilities. This recognition is a testament to its commitment to striving for excellence and continuing towards the pinnacle of academic eminence.